2021
DOI: 10.1002/anbr.202100090
|View full text |Cite
|
Sign up to set email alerts
|

Interconnectivity Explains High Canalicular Network Robustness between Neighboring Osteocyte Lacunae in Human Bone

Abstract: Osteocytes are the most frequent bone cells connected with each other through cell processes within tiny tubular-shaped canaliculi. The so-called osteocyte lacunar-canalicular network (LCN) plays a crucial role in bone remodeling and mineral homeostasis. Given the critical nature of these functions, it is herein hypothesized that the LCN must be structurally "overengineered" to provide network resilience. This hypothesis is tested by characterizing canalicular networks in human bone at the fundamental "buildin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…To date, however, virtually all simulations of permeability of human bone porosities have been limited to vascular and LCN pores. (22,44,58,59) The discovery of a subcanalicular network in bone reported in the present study is an additional factor in this context. It should be noted that nanoscale porosity that gives rise to bone poroelasticity and interstitial fluid permeability has been noted in the published literature.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…To date, however, virtually all simulations of permeability of human bone porosities have been limited to vascular and LCN pores. (22,44,58,59) The discovery of a subcanalicular network in bone reported in the present study is an additional factor in this context. It should be noted that nanoscale porosity that gives rise to bone poroelasticity and interstitial fluid permeability has been noted in the published literature.…”
Section: Discussionsupporting
confidence: 52%
“…The LCN volume and surface area have implications for bone mineralization as they provide extracellular matrix access to ions and small molecules. (20) 3D imaging of the bone LCN using synchrotron radiation phase-contrast nano-CT (21,22) and confocal microscopy (23) has revealed that 50% of the mineralized tissue in the human skeleton is located within $1.5 μm of the closest LCN boundary and 80% within 2 to 3 μm. Further, a recent FIB-SEM examination of forming human bone suggests co-diffusion of mineralization precursors, promotors, and inhibitors from the LCN to the bone matrix, (24) an observation highlighting the role of the LCN in supporting and achieving mineral homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, if all angles were randomly distributed, there would be no peak in the histogram, and thus the variance would be the smallest. Since the angles are interrelated, we define the product of the variances as a descriptor for the alignment, called the level of alignment (LOA) (Bortel et al, 2022).…”
Section: Arrangement Of the Intracortical Pore Systemmentioning
confidence: 99%
“…Through Darcy's law, the fluid and flow were computed. To numerically estimate the absolute permeability, the Stokes equations are applied (Bortel et al, 2022).…”
Section: Fluid Simulationmentioning
confidence: 99%
“…Although the LCN contributes less to overall bone porosity compared with blood vessel pores (Haversian and Volkmann canals), the surface area formed by the LCN is more than one order of magnitude larger than the surface formed by blood vessel pores (Hesse et al, 2015). Mineral exchange is likely to occur at all bone interfaces including blood vessel pores and at the LCN (Ayoubi et al, 2020;Bortel et al, 2021;Vahidi et al, 2021). The role of the osteocyte network, housed inside the LCN, is not only to contribute to mineral homeostasis through exchange of ions at their mineral interfaces but also in mechano-transduction and subsequent triggering of osteoblast/osteoclast remodeling (Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%